2018
DOI: 10.1186/s12882-018-0933-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for infectious complications of ANCA-associated vasculitis: a cohort study

Abstract: BackgroundSevere infections are common complications of immunosuppressive treatment for antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) with renal involvement. We investigated the clinical characteristics and risk factors of severe infection in Chinese patients with AAV after immunosuppressive therapy.MethodsA total of 248 patients with a new diagnosis of ANCA-associated vasculitis were included in this study. The incidence, time, site, and risk factors of severe infection by the inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
59
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 33 publications
8
59
0
4
Order By: Relevance
“…In this study, older age, high dosages of CS, and CS pulse therapy were identified as significant risk factors for OIs. The findings of previous studies were in line with our results, and showed that older age and CS use were associated with serious infections, including OIs, in patients with AAV . Elderly patients are generally vulnerable to infections, and CS use increases the risk of infections .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, older age, high dosages of CS, and CS pulse therapy were identified as significant risk factors for OIs. The findings of previous studies were in line with our results, and showed that older age and CS use were associated with serious infections, including OIs, in patients with AAV . Elderly patients are generally vulnerable to infections, and CS use increases the risk of infections .…”
Section: Discussionsupporting
confidence: 92%
“…There are several reports showing that patients with AAV have a high risk of infection. About 20%‐60% of patients with AAV developed infections, and respiratory infection was the most frequent . An observational cohort study conducted in Japan also revealed that serious infections occurred in about 27% of patients with AAV during remission‐induction therapy .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to population controls, the rate ratio for serious infections was 4.5 in a study from southern Sweden [275] and the risk of hospitalization due to infections was increased almost ten times in a study from Denmark [276]. Although the aim of Paper IV was not to study infections, we did find that it was the most common cause of both death and readmission, in line with the increased risk of infections in AAV, seen especially with higher age and renal impairment [269,272,275,277].…”
Section: Cause Of Deathmentioning
confidence: 66%
“…The incidence of infection during induction therapy was 36.0% (41/114) in CYCLOPS study [5] and was 39.0% for glucocorticoids in combination with intravenous cyclophosphamide (IV-CYC) in a Chinese cohort [8].…”
mentioning
confidence: 99%